Features of Self-Perception in Men and Women Suffering from Alcohol Addiction - Vlasova, N.V.; Buslaeva, E.L. (Psihologiâ i pravo, 2027)
The article presents results of the research into self-perception of males and females diagnosed with chronic alcoholism. The article's data is theoretically based on the analysis of contemporary scientific studies which indicate a number of discrepancies identified in certain qualitative characteristics of alcohol addicts' self-image. The empirical research studies 80 people aged between 30 and 47 years, including males (N = 20) and females (N = 20) with alcohol addiction, as well as healthy males (N = 20) and females (N = 20) who consume alcohol not more than 3 times a month. To identify indicators of a person's self-perception the article uses the following methodology: "The study of the general self-esteem" by G.N. Kazantseva, "Personality differential" by E.F. Bazhin and A.M. Etkind, "Self-attitude Questionnaire" by V.V. Stolin and S.R. Pantileev. The research data shows that male alcohol addicts tend to have low self-esteem and self-control, declining auto-sympathy and self-acceptance, lack of self-management which is paradoxically coupled with excessive self-assurance. At the same time female alcohol addicts self-image is less different from that of healthy females. The former tend to have excessive self-assurance combined with low self-understanding. Moreover, compared with their male counterparts, females alcohol users show higher auto-sympathy and lower self-blaming. The acquired data can be used for developing rehabilitation programs for people suffering from alcohol addiction to help them build motivation for alcohol withdrawal. В статье приведены результаты исследования компонентов самовосприятия мужчин и женщин с установленным диагнозом хронический алкоголизм. Теоретическим обоснованием работы выступает анализ современных научных исследований, который указывает на ряд противоречий, выявленных при изучении отдельных качественных характеристик в самооценке лиц с алкогольной зависимостью. В эмпирическом исследовании приняли участие 80 человек в возрасте от 30 до 47 лет, в том числе алкозависимые женщины (N 20) и мужчины (N = 20), а также здоровые женщины (N = 20) и мужчины (N = 20), употребляющие спиртные напитки не чаще 2-3 раз в месяц. Для определения показателей самовосприятия личности были использованы следующие методики: «Изучение общей самооценки» (Г.Н. Казанцева), «Личностный дифференциал» (Е.Ф. Бажин и А.М. Эткинд), «Тест-опросник самоотношения» (В.В. Столин и С.Р. Пантилеев). Результаты исследования показали, что характерными чертами самовосприятия у мужчин с алкогольной зависимостью является низкий уровень самооценки и самоконтроля, снижение аутосимпатии и самопринятия, отсутствие ощущения саморуководства в парадоксальном сочетании с излишней самоуверенностью. В то же время самовосприятие женщин с алкогольной зависимостью в меньшей степени отличается от показателей здоровых респонденток и характеризуется излишней самоуверенностью в сочетании с низким самопониманием. Кроме того, в отличие от алкозависимых мужчин страдающие алкоголизмом женщины испытывают большую аутосимпатию и менее выраженный уровень самообвинения. Полученные данные могут быть использованы для разработки программ реабилитации, направленных на формирование мотивации отказа от употребления алкоголя у лиц, страдающих алкозависимостью.